SERUM IRON INDICES IN VARIOUS TYPES OF ACUTE INFECTION. - ELI MOHAPATRA (International Journal of Pharma and Bio Sciences, 2013)
Objective of this paper is to describe how iron indices ie Serum iron concentration and Total iron binding capacity are effected during acute infection. Previousely, the work was done on the affect of Acute bacterial infection on Serum iron indices .It was observed that both were reduced .Because micro-organism invades our body and utilises iron for their growth and multiplication. Though ,iron comes under the group of trace element but plays a very important role in our body. A total of 120 patient were taken out of which 50 were healthy control and 70 were those with acute bacterial , viral and protozoal infection. It was observed that there was significant reduction in Serum iron indices as compared to control.And the total protein was slightly high. . Knowledge of these interactions is essential in assessing likely morbidity responses to iron supplementation.